Cystic Fibrosis Diagnosis in Newborns, Children, and Adults - Castellani, Carlo; Linnane, Barry; Pranke, Iwona; Cresta, Federico; Sermet-Gaudelus, Isabelle; Peckham, Daniel (Seminars in Respiratory and Critical Care Medicine, 2019)
The diagnosis of cystic fibrosis (CF) has traditionally relied on the presence of clinical features of the disease. Today, diagnosis through newborn screening (NBS) is becoming the standard of modern CF care. CF NBS programs can identify CF prior to clinical presentation, but for the advantages of an early diagnosis to accrue a scrupulous system must be in place to ensure all steps in the program are performing. As we move rapidly into the era of CF transmembrane conductance regulator (CFTR) protein modulators, the opportunity to start a presymptomatic infant, identified through CF NBS, on these agents offers the prospect of true disease-modifying interventions which could result in a paradigm shift in CF care.Conversely, the introduction of NBS has resulted in many children being asymptomatic at the time of diagnosis. Some screened newborns are classified as “CF Screening Positive, Inconclusive Diagnosis”, or “CFTR-related metabolic syndrome” when the diagnosis can neither be confirmed nor excluded. Appropriate assessment and follow-up should be arranged at specialist centers as a proportion of these infants and adults will eventually be diagnosed with CF.Symptoms and signs are particularly pertinent when considering a diagnosis of CF outside the context of NBS. In older patients with a late diagnosis, the spectrum of clinical presentation can be very variable with vigilant clinicians from multiple specialties suspecting the diagnosis in conditions such as recurrent pulmonary infections, male infertility, pancreatitis, nasal polyposis, and malabsorption.In addition to clinical symptoms or positive NBS results, sweat test and genetic analysis are cornerstones in the diagnosis of CF, but in some cases the diagnosis cannot be confirmed on genetic or sweat testing. Difficult diagnosis may be supported by in vivo or ex vivo electrophysiology measurements on respiratory or intestinal epithelia. This can be done by either measuring transepithelial nasal potential difference or intestinal current measurements.
Keywords: cystic fibrosis; diagnosis; CFTR; sweat test; newborn screening; CFSPID; immunoreactive trypsinogen; nasal potential difference